2020
DOI: 10.18844/wjet.v12i3.5000
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in education technologies research worldwide: Meta-analysis of studies between 2015-2020

Abstract: The interaction of education and technology affects the developments occurring in two areas and the development in education increases the speed of technological developments. Educational technology is the functionalization of the scientific knowledge produced in educational sciences and its application into practice. In this research, the content analysis of the studies conducted in Turkey and other countries in the last 5 years is presented in order to determine the current trends in Educational Technology R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In addition, they kept quiet to signal their awareness of the phrase usage that demands the speaker to continue talking than repeat the utterance in this instance. The finding supports Yildiz, et al (2020) who indicate that students express a positive opinion about the effectiveness of using videoconference lessons. This suggests that videoconferencing is a suitable strategy for learning conversational English online, but it must be used appropriately since there is a huge distance between the lectures and their students.…”
Section: Findings and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, they kept quiet to signal their awareness of the phrase usage that demands the speaker to continue talking than repeat the utterance in this instance. The finding supports Yildiz, et al (2020) who indicate that students express a positive opinion about the effectiveness of using videoconference lessons. This suggests that videoconferencing is a suitable strategy for learning conversational English online, but it must be used appropriately since there is a huge distance between the lectures and their students.…”
Section: Findings and Discussionsupporting
confidence: 81%
“…This has been the situation regardless of constraints in the implementation of online teaching and learning such as internet connectivity and lack of internet facilities. In this situation, students expressed a positive opinion about the effectiveness of online education (Yildiz, Cengel, & Alkan, 2020). Most of the students develop paraphrasing ideas, evaluating, and comparing tactics as well as supporting them with evidence, innovativeness, and creativity.…”
Section: Introductionmentioning
confidence: 98%
“…Considering the distribution of studies on the themes searched in the Web of Science database by country, it was found that the country with the most studies was Spain (12), followed by the People's Republic of China (25) and Australia (19).…”
Section: Findings Of the Documents By Countriesmentioning
confidence: 99%
“…The term 'educational technology' emphasises a discipline related to learning and teaching processes. On the other hand, the term 'instructional technology' expresses the effectiveness of guiding learning in teaching a subject [25] [24].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of education is to transfer the culture that marks the society from generation to generation (Değirmenci, 2007;Konst, & Kairisto-Mertanen, 2019). The aim of the education system today is to provide effective education, to create the necessary environment for its students, to provide the determined gains, to support the student's learning by living and to enable them to use these teachings in the future life (Shkola, Zhamardiy, Saienko, Tolchieva & Poluliashchenko, 2020;Yildiz, Cengel, & Alkan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%